MUHAMMADIYAH- NAHDLATUL ULAMA (NU): MONUMENTAL CULTURAL CREATIVITY HERITAGE OF THE WORLD RELIGION - Maman A. Majid B; Somariah F; Sintha W (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2018)
Muhammadiyah and NU are two well-known socio-religious organizations in the world over the years. In spite of the fact that both organizations are characterized as religious social movement, each of them has their individual creativity, which is called al-thaqafat in their motions. This study aims to identify the organization of Muhammadiyah-NU as a religious heritage,which affects other religious organizations both in Indonesia and other countries. This research employed a qualitative approach by using historical method to obtain the actual reality. For data collection, literature reviews,documentation and interviews were also conducted to gather empiric facts.The researchers interviewed public figures of the organizations. Al-thaqafat becomes part of elements rather than cultivated culture, which is understood as habitual patterns of human creativity, including a religious organization. Both organizations are the result of an al-thaqafat religious creativity created by each founder and can be pursued into the world monumental heritage. Without denying, the existence of al-thaqafat creativity will continue to enlighten the world civilization. Therefore, Muhammadiyah and NU have been doing and keeping continuing al-thaqafat creativity enlightenment through their charitable organizations and institutions. The result is profoundly proven so that they have been in an existence more than a century.